Papinniemi i Uukuniemi och andra ortodoxa gravfält i östra Finland: Utgångspunkter och aktuell forskningsproblematik - Laakso, Ville (Hikuin, 2003)
Papinniemi in Uukuniemi and other orthodox village cemeteries in Eastern Finland – basis for and problems of research By Ville Laakso At the turn of the 16th and 17th centuries Sweden conquered an area in Karelia known as the Käkisalmi Province (fig. 1). The people living in this area were Greek orthodox Karelians, and their culture was somewhat different from the Lutheran population of the Swedish state. Because of Lutheranization and heavy taxation, majority of this orthodox population moved to Russia during the 17th century. Today part of this area is Finland, part of it was ceded by Soviet Union during the Second World War. From an archaeological point of view, characteristic for this cultural area is the use of village cemeteries. There are probably a few hundred of them in the area, but there is still very little research material of these sites. They date mainly from 14th to 17th centuries, some of them have been in use until the 19th or even 20th century. Research problems of the cemeteries include lack of systematic surveys and larger excavations, poor documentation of early fieldwork, and lack of datings from unfurnished graves. On the other hand, there is rich oral tradition as well as some ethnographic data and written sources that provide us with information about these sites. Systematic archaeological surveys and excavations of the cemeteries have recently been started in Eastern Finland. Future themes of research are for example comparison between different categories of source material connected with these sites, christianization of the area, details of orthodox burial customs, and the historical orthodox cultural landscape. The most extensive archaeological excavations in connection with this cultural phase have been conducted by the University of Turku at the deserted village of Papinniemi in the parish of Uukuniemi, Eastern Finland. There has been an orthodox church, a cemetery and several houses in the area, which has been completely deserted since the mid-17th century.